Protection of Women's Rights After Divorce in Religious Courts: What Makes this Mission Difficult to Achieve? - Yuni, Lilik Andar; Haries, Akhmad (Fakultas Syariah UINSI Samarinda, 2024)
The normative assurance of protection for women's and children's rights post-divorce has been extensively regulated through laws, including the Compilation of Islamic Law (KHI), the Supreme Court Regulation (PERMA), and the Supreme Court Circular Letter (SEMA). However, not all these regulations have been effectively implemented post-divorce in Indonesian Religious Courts. Hence, this article is written to understand how the implementation of post-divorce women's rights protection occurs in the Religious Courts, especially when the husbands are absent from the divorce trials (verstek judgments). This normative-doctrinal legal research utilizes the statutory and case law analysis of selected decisions from Samarinda and Sangatta Religious Courts. The findings indicate that the protection of post-divorce women's rights is not adequately realized, as not all the rights of former wives in the Religious Courts are adequately accommodated, especially the alimony (nafkah iddah). This is attributed to cases being decided in absentia of the husband, indications of the wife's disobedience (nushuz), low awareness of the wife regarding her rights, and the gender sensitivity of the judges not being maximum.